Study of interaction between plasma flows and the magnetic field at the implosion of nested wire arrays. (23rd January 2019) - Aleksandrov, V V; Branitski, A V; Gasilov, V A; Grabovskiy, E V; Gritsuk, A N; Mitrofanov, K N; Olkhovskaya, O G; Sasorov, P V; Frolov, I N
Abstract: At the Angara-5-1 facility investigation was carried out which studied the interaction of plasma flows and the magnetic field. They are created by the current implosion of cylindrical nested wire arrays, the inner and outer array of which are composed from thin wires or dielectric fibers. It has been shown experimentally that at the plasma formation stage it is possible to realize various modes of interaction between plasma flows and the magnetic field of the discharge current inside the nested array. A mechanism is proposed for the interaction of plasma flows of the outer array with the magnetic field and the current-carrying plasma of the inner array. The stability of the plasma compression of the inner array at the final stage of its compression depends on the nature of this interaction. Obtained experimental data on the dynamics of interaction of plasma flows with the magnetic field in the gap between arrays are compared with the results of 2D-simulation of the implosion of nested arrays according to the RMHD MARPLE code. It is experimentally and theoretically confirmed that when a nested array is imploded with certain parameters around the inner array, a plasma quasi-closed shell is formed in the azimuthal direction.